The influence of anisotropic tissue expander on nestin and TrKB expression in rat Cranio-Facial region / Aminah Jalil - Aminah, Jalil (2019)
Introduction: Skin is a highly dynamic, autoregulated, living system that responds to mechanical stretch providing a net gain in skin surface area. The techniques for expanding skin and soft tissues are widely used to repair damaged tissues and to facilitate the provision of new additional skin tissue with similar quality, texture and color. Little is known regarding the effect of tissue expansion on peripheral nerve. Should the new nerve could be generated by this method without significant damage then the additional skin generated may present with the similar sensation as the adjacent skin. Objective: (1) To compare the histological changes between non-expanded and expanded tissues in a rat model implanted with anisotropic tissue expander. (2) To investigate the presence of nestin and TrkB protein marker expression in expanded and non-expanded tissues. Method: Twenty adult female Sprague Dawley rats 180-220 g were used in this study. Ten anisotropic controlled rate self-inflating tissue expanders (Oxtex, UK) were implanted subcutaneously at the scalp region under general anaethesia. After 28 days, animals were euthanized, the expanders were explanted and expanded skin were harvested. Immunohistochemistry was performed to detect the presence of nestin (Rat 401) Mouse mAb) (CST) and TrkB (NT-3) expression. (CST). Results: Nestin immune-positive staining was found on the expanded skin, while TrkB expression was comparable to the normal skin. v Conclusion: Tissue expansion using anisotropic self-inflating tissue expander resulted in expansion of the skin tissue with possibility of similar innervation and histological texture that resembles the control tissue. Keywords: peripheral nerve, Nestin, TrkB, anisotropic tissue expander, epidermis, dermis.